Characteristics of Series and Parallel Centrifugal Pumps - Andrian Saputro; Denny Prumanto; Muhammad Sheva Ramadhan (Greenation International Journal of Engineering Science, 2026)
A pump is a device used to lift fluids from a lower surface to a higher surface and to move fluids from low pressure to higher pressure. One such device is a centrifugal pump, a dynamic pressure pump widely used to move fluids with high head. The fluids that can be moved are incompressible fluids. In specific applications, pumps can be used to move substances like this centrifugal pump, this is done so that we can use the tool.